British Council’s English for Academic Purposes: A Critical Analysis of the Coursebook Taught at Pakistani Universities - Abdul Qadir (University of Chitral Journal of Linguistics and Literature, 2019)
English for Academic Purposes course focusing on the academic language needsof students is a subfield of English for Specific Purposes (ESP). It is a type ofspecialized course to integrate specific subject matter, language content, andmaterial based on learners’ needs. The study aims to evaluate the BritishCouncil’s English for Academic Purposes (EAP) coursebook in terms of content,sequencing, learners’ autonomy, motivation, feedback and focus on languageskills. Furthermore, the study tries to provide a general perception of theusefulness and effectiveness of the coursebook for undergraduate students. TheEAP Students’ Manual coursebook is used as a primary source for the datacollection. The researcher has chosen Nation & Macalister (2010) model oflanguage teaching principles to analyze and discuss the data. The study found thecoursebook a useful, effective and an appropriate source of English languagelearning in terms of the investigated aspects of the book. The findings report thatthe coursebook provides practice and practical usage in all domains of theacademically required English language skills. It helps the students to buildlanguage competency and to be more independent learners. In addition, itprovides an opportunity to the learners to think in the target language, use thelanguage more practically and learn it in a natural type of environment. The studyconcludes and suggests that the content needs to be supplemented with Englishlanguage audios and videos presenting the students relevant documentaries andhelping material in order to make the coursebook and the learning process moreuseful, effective, interesting and motivating. Furthermore, the study recommendsthat while choosing /designing a coursebook for a certain course, it needs to beevaluated following the various criteria and language-teaching-principlessuggested by different language researchers.